2023
DOI: 10.3390/ma16062516
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Green Part of Steel from Metal Injection Molding: An Analysis Using Moldflow

Abstract: Metal injection molding (MIM) is a quick manufacturing method that produces elaborate and complex items accurately and repeatably. The success of MIM is highly impacted by green part characteristics. This work characterized the green part of steel produced using MIM from feedstock with a powder/binder ratio of 93:7. Several parameters were used, such as dual gates position, injection temperature of ~150 °C, and injection pressure of ~180 MPa. Analysis using Moldflow revealed that the aformentioned parameters w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…Metal injection molding is an advanced manufacturing technique that allows the molding of metal parts with complex shapes and precise dimensions using a process similar to traditional plastic injection molding [194,195]. Taking a rheological approach, the feedstock for metal-IM technology is a suspension.…”
Section: Metal Injection Moldingmentioning
confidence: 99%
“…Metal injection molding is an advanced manufacturing technique that allows the molding of metal parts with complex shapes and precise dimensions using a process similar to traditional plastic injection molding [194,195]. Taking a rheological approach, the feedstock for metal-IM technology is a suspension.…”
Section: Metal Injection Moldingmentioning
confidence: 99%
“…First, the B part was considered as the most sophisticated shape as compared to the other two parts. It was suggested that positioning the gate near the part with a high sophistication would minimize the possibility of an undesirable phenomenon happening [28,31,32]. Secondly, The computational analysis conducted in this study is associated with the specific parameters employed, especially the gate location, injection pressure, and injection temperature.…”
Section: Moldflow Analysismentioning
confidence: 99%
“…Based on this, the present study employs Metal Injection Molding [11][12][13][14][15][16] (MIM) technology and designs experiments based on factorial design [17], producing gears and using a 3D structured light scanner to collect point cloud data of all gear shapes throughout the MIM process, thereby constructing a dataset containing 1101 point cloud datasets of small gears. Subsequently, the gears are manually annotated and segmented.…”
Section: Introductionmentioning
confidence: 99%